Social Assistance Recipient Program Based on Lawrence M. Friedman's Theory - Magna, Merlin Swantamalo; Karisma, Seli (Journal of Law, Politic and Humanities, 2025)
Poverty is a multidimensional problem that has a wide impact on various aspects of people's lives. One of the government's main strategies in overcoming this problem is through the provision of social assistance (bansos). However, in its implementation, there are still social assistance recipients who are not on target, so improvements are needed in the requirements for aid recipients. This study explores social assistance receipt programs within the framework of Lawrence M. Friedman's legal system theory, which highlights three main components in the legal system: legal structure, legal substance, and legal culture. Using normative methods and conceptual approaches, this research relies on secondary data from relevant regulations, policies, and academic literature. The findings of the study reveal that although the legal structure that regulates social assistance is available formally and completely, in the sub-system of legal substance, it is necessary to determine more detailed and objective criteria for social assistance recipients so as to minimize recipients of assistance that are not on target. In addition, the legal culture shows the phenomenon of people who tend to represent themselves as poor individuals so that they deserve social assistance. Therefore, it is necessary to work together from the government and the community through changes in legal culture; mindset and habits so that they can form an effective legal structure and legal substance as an effort to alleviate poverty in Indonesia.